Synthesis, computational study and biological evaluation of 9-acridinyl and 1-coumarinyl-1,2,3-triazole-4-yl derivatives as topoisomerase II inhibitors - Gehan A. Abdel-Hafez; Abdel-Maaboud I. Mohamed; Adel F. Youssef; Claire Simons; Ahmed S. Aboraia (Taylor & Francis Group, 2022)
Topoisomerase (IIB) inhibitors have been involved in the therapies of tumour progression and have become a major focus for the development of anticancer agents. New three-component hybridised ligands, 1,4-disubstituted-1,2,3-triazoles (8-17), were synthesised via a 1,3-dipolar cycloaddition reaction of 9-azidoacridine/3-azidocoumarin with N/O-propargyl small molecules under click reaction conditions. Cancer cell growth inhibition of the synthesised triazoles was tested against human cell-lines in the NCI-60-cell-panel, and the most active compounds tested against topoisomerase (IIB)-enzymes. The acridinyl ligands (8-10) revealed 60-97% cell growth inhibition in six cancer cell-panels. Cell-cycle analysis of MCF7 and DU-145 cells treated with the active acridinyl ligands exhibited cell-cycle arrest at G2/M phase and proapoptotic activity. In addition, compound 8 displayed greater inhibitory activity against topoisomerase (IIB) (IC50 0.52 µM) compared with doxorubicin (IC50 0.83 µM). Molecular dynamics simulation studies showed the acridine-triazole-pyrimidine hybrid pharmacophore was optimal with respect to protein-ligand interaction and fit within the binding site, with optimal orientation to allow for intercalation with the DNA bases (DG13, DC14, and DT9).